2006
DOI: 10.3201/eid1206.051097
|View full text |Cite
|
Sign up to set email alerts
|

VIM-1 Metallo-β-lactamase inAcinetobacter baumannii

Abstract: In 2004 and 2005, 5 metallo-β-lactamase (MBL)-positive Acinetobacter baumannii isolates were found in 2 Greek hospitals. Isolates were unrelated and carried blaVIM-1 in a class 1 integron; blaOXA-51- and blaOXA-58-like carbapenemase genes were also detected. VIM-1 MBL in Acinetobacter spp. causes concern, given the increasing resistance of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 15 publications
3
65
0
5
Order By: Relevance
“…Of the five MBL groups described to date (589), only three have been identified in A. baumannii, including IMP (89,104,113,179,246,265,298,316,402,471,506,530,544,618), VIM (316,335,551,606,615), and SIM (320) types. Several geographic regions, such as Spain, Singapore, Greece, and Australia, have shown the presence of both OXA-and MBLtype enzymes in the same strains (70,298,423,551). Unlike the OXA-type enzymes, MBLs are most commonly found within integrons, which are specialized genetic structures that facilitate the acquisition and expression (via a common promoter) of resistance determinants.…”
Section: ␤-Lactamsmentioning
confidence: 99%
“…Of the five MBL groups described to date (589), only three have been identified in A. baumannii, including IMP (89,104,113,179,246,265,298,316,402,471,506,530,544,618), VIM (316,335,551,606,615), and SIM (320) types. Several geographic regions, such as Spain, Singapore, Greece, and Australia, have shown the presence of both OXA-and MBLtype enzymes in the same strains (70,298,423,551). Unlike the OXA-type enzymes, MBLs are most commonly found within integrons, which are specialized genetic structures that facilitate the acquisition and expression (via a common promoter) of resistance determinants.…”
Section: ␤-Lactamsmentioning
confidence: 99%
“…However, despite the worldwide occurrence of epidemic carbapenem-resistant strains, MBL-producing A. baumannii isolates have been found to be disseminated only in specific geographic areas (8,10). In Greek hospitals high rates of carbapenem-resistant A. baumannii clinical isolates are also detected, but MBL producers have been recognized in only a few instances (12). Therefore, the detection of these enzymes is of major importance in the control of A. baumannii hospital infections.…”
mentioning
confidence: 99%
“…VIM-2-producing Acinetobacter spp. have been isolated in the Far East (Lee, et al, 2003) and in Germany (Toleman, 2004), while the VIM-1 determinant has been reported only in Greece (Tsakris 2006). One study recently identified VIM-4, which is nothing but a point mutant of VIM-1 and that has been previously identified only in Enterobacteriaceae (Luzzaro et al, 2008) and Pseudomonas spp.…”
Section: B-classmentioning
confidence: 99%
“…Concurrently, it was also observed in Greece that blaVIM-1 which is widespread in P. aeruginosa had apparently crossed the species barrier to reach Acinetobacter spp. Such examples might be yet another example of resistance genes crossing genus barrier (Tsakris et al, 2006).…”
Section: B-classmentioning
confidence: 99%